1993
DOI: 10.1063/1.464538
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the reactions of O(1D) with HCl, DCl, and Cl2

Abstract: The reactions O('D)+HCI->OH+CI (1a) and OCI+H (1b), O('D)+DCl->OD+CI (2a) and OCI+D (2b), and 0(,D)+CI 2->OCI+CI (3) are studied at an average collision energy of 7.6, 7.7, and 8.8 kcal/mol for (1), (2), and (3), respectively. H, D, and CI atoms are detected by the resonance-enhanced multiphoton ionization technique. The average kinetic energies released to the products are estimated from Doppler profile measurements of the product atoms. The relative yields [OCI+H]/[OH+CI] and [OCI+D]/[OD+CI] are directly mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
49
0
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 17 publications
9
49
0
2
Order By: Relevance
“…Both the spin-orbit excited ( 2 P J = 1/2 ) and ground ( 2 P J = 3/2 ) states of Cl were observed in the OH + Cl channel; [4,31] the yield of Cl*A C H T U N G T R E N N U N G ( 2 P 1/2 ) was found to be less than half of the degeneracy ratio between 2 P 1/2 and 2 P 3/2 , which indicates that an adiabatic reaction pathway leading to 2 P 3/2 is important. On the basis of the state-correlation diagram for 2 P W = 1/2, 3/2 (OH) and 2 P J = 3/2, 1/2 (Cl) in the linear geometry, Matsumi et al [4] suggested that the Cl*A C H T U N G T R E N N U N G ( Herein, we attempt to address some of these issues by the first measurement of the differential cross sections for the title reaction.…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…Both the spin-orbit excited ( 2 P J = 1/2 ) and ground ( 2 P J = 3/2 ) states of Cl were observed in the OH + Cl channel; [4,31] the yield of Cl*A C H T U N G T R E N N U N G ( 2 P 1/2 ) was found to be less than half of the degeneracy ratio between 2 P 1/2 and 2 P 3/2 , which indicates that an adiabatic reaction pathway leading to 2 P 3/2 is important. On the basis of the state-correlation diagram for 2 P W = 1/2, 3/2 (OH) and 2 P J = 3/2, 1/2 (Cl) in the linear geometry, Matsumi et al [4] suggested that the Cl*A C H T U N G T R E N N U N G ( Herein, we attempt to address some of these issues by the first measurement of the differential cross sections for the title reaction.…”
mentioning
confidence: 98%
“…The high reactivity originates from an open-shell electronic configuration in the singlet state, which allows the O atom to insert into a chemical bond without a reaction barrier. The insertion results in a deep well on the ground-state potential energy surface (PES), which corresponds to stable species of H 2 O (X In addition to the ground-state pathway, recent experimental and theoretical studies [1][2][3] have revealed an abstraction process on the excited-state PESs with small reaction barriers [ % 2 kcal mol À1 for OA C H T U N G T R E N N U N G ( ) was measured by Matsumi et al [4] to be % 1:4 in a bulb experiment at the average collision energy of 7.6 kcal mol…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction of electronically excited oxygen with hydrochloric acid has been a focus of several experimental [1][2][3][4][5][6][7][8][9] and theoretical studies. The reaction plays an important role in the modeling of atmospheric chemistry and presents an interesting system for the study of fundamental dynamics.…”
Section: Introductionmentioning
confidence: 99%